(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Zanthoxylum armatum DC., belonged to the family Ruteacea, is a medicinal plant used to cure many diseases. DNA barcoding was used as a tool for molecular identification of Zanthoxylum armatum DC. species from Balakot Pakistan. In the present study four DNA barcodes including matk, rbcl, ITS and trnH-psbA were used. The sequenced data were analyzed by using BLASTn at NCBI, FASTA and Mega 7.0 software. During PCR analysis, 3 DNA barcodes ITS, rbcl and trnh-psbA were successfully amplified and showed the 100% sequencing success. Furthermore, these barcode markers showed 99-100% sequence similarity with the reference sequences at the BLASTn. The further analysis revealed the sequence similarity of investigating marker with Zanthoxylum armatum (MH016484.1), Zanthoxylum nitidum (FN599471.1) and Zanthoxylum bungeanum (MF097123.1) respectively. The current finding provides the basis for sequenced data of Z. armatum to be used in future for molecular discrimination among the plant species from Pakistan and it is concluded that combination of diverse kind of barcoding markers could be helpful in proper identification of species at lower taxonomic level. Bangladesh J. Plant Taxon. 27(2): 323-333, 2020 (December)